Relationship between AUM and Alpha in SA mutual funds - Ziphethe-Makola, Sandiswa Masande (Research of GSB, 2018)
Academics and financial media are divided on whether the size of assets under management (AUM) influences returns. In an attempt to seek clarity in the local context, this study investigates the effect of the size of assets under management on alpha in South African equity mutual funds over the three-year period to 31 December 2015. The study is based on secondary quantitative data reported on the Bloomberg Professional service database that includes mutual fund and benchmark indices, unit prices and fund asset sizes. The research sample comprises 69 South African equity mutual funds that existed for the three-year period under review. In this study, the relationship between AUM size and alpha is examined using the cross-sectional regression approach. No evidence of a linear relationship between AUM size and alpha was observed in the analysis based on the sample data. This finding is consistent with the semi-strong form efficient market hypothesis that securities reflect publicly available information. This finding implies that the exponential growth in AUM experienced in South Africa over the past two decades has neither enhanced nor come at the cost of returns. There does not seem to be a size effect that new investors and fund managers should be aware of.